Hubungan Kadar Trombosit dengan Gambaran Luas Lesi Tuberkulosis Paru melalui Foto Chest X-Ray - Alimsjah, Yohanes Audric; Yueniwati, Yuyun; Nugroho, Rafiq Sulistyo (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Background: Pulmonary tuberculosis (TB) is a chronic inflammatory disease accompanied by changes in particular haematological parameters within the blood. The changes in the composition of blood cells can be potential biomarkers to assist tuberculosis diagnosis beside using clinical, microbiological, and radiological tools. Platelets play a vital part in chronic inflammation since they contain different sorts of mediators that are involved in lung damage which is reflected in the extent of lesions on radiological examination. Aim: The research aims to compare the platelets level between minimal/moderate versus extensive lesions in the patient with TB. Methods: The research was a retrospective, cross-sectional study of patients with pulmonary tuberculosis who were treated at Saiful Anwar Hospital from January 2022 to December 2023. The results of the research were analyzed using the Chi-Square method. Results: Patients with extensive pulmonary TB lesions have platelet levels that tend to be high, in contrast to patients with minimal/moderate pulmonary TB lesions tend to have low platelet levels. Conclusion: There was a significant relationship between platelet levels and the extent of pulmonary tuberculosis lesions.